2009
DOI: 10.1007/s11262-009-0341-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and membrane integration of SARS-CoV E protein and its interaction with M protein

Abstract: The severe acute respiratory syndrome (SARS)-CoV E gene fragment was cloned and expressed as a recombinant protein fused with a myc tag at the N-terminus in vitro and in Vero E6 cells. Similar to other N-glycosylated proteins, the glycosylation of SARS-CoV E protein occurred co-translationally in the presence of microsomes. The SARS-CoV E protein is predicted to be a double-spanning membrane protein lacking a conventional signal peptide. Both of the transmembrane regions (a.a. 11-33 and 37-59) are predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It should be pointed out that HA peptide was fused to the C terminus of the M protein, which is considered to be the essential for M-M interaction and VLP assembly [10,12,18,29,54,55]. Several groups reported that deletion, substitution or extension of the C terminus of the M protein affects interaction with other proteins [6,8,18,[56][57][58]. M protein of most coronaviral species exposes its N-terminus outside the virion, whereas the C-terminal tail is hidden inside the particle (N exo -C endo orientation).…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that HA peptide was fused to the C terminus of the M protein, which is considered to be the essential for M-M interaction and VLP assembly [10,12,18,29,54,55]. Several groups reported that deletion, substitution or extension of the C terminus of the M protein affects interaction with other proteins [6,8,18,[56][57][58]. M protein of most coronaviral species exposes its N-terminus outside the virion, whereas the C-terminal tail is hidden inside the particle (N exo -C endo orientation).…”
Section: Discussionmentioning
confidence: 99%
“…In an alternative minor form, SARS-CoV E protein was shown to be glycosylated on N66, with the C-terminus exposed to the luminal side [80]. A later study using transfected SARS-CoV E protein with an N-terminal Myc-tag confirmed that SARS-CoV E protein was glycosylated co-translationally [83]. Although the two putative TM domains were required for its interaction with the SARS-CoV M protein, the hydrophilic region (60-76) flanking the N66 glycosylation site was dispensable as shown by co-immunoprecipitation experiment [83].…”
Section: Glycosylationmentioning
confidence: 96%
“…Incubate the protein samples with magnetic beads by endover-end rotation overnight at 4 °C. 13. Wash the magnetic beads three times with 1 ml modifi ed RIPA buffer.…”
Section: Cells (Frommentioning
confidence: 99%